'A Deepfake Porn Plot Intended to Silence Me': exploring continuities between pornographic and 'political' deep fakes. Issue 4 (1st October 2020) - Maddocks, Sophie
ABSTRACT: 'Deep fakes' went viral in 2017 when artificial intelligence-manipulated porn was uploaded to the discussion website Reddit. Within a month, tens of thousands of people had followed suit and shared their own 'deep fake' porn on the site. The majority of deep fakes that circulate online today are pornographic, yet public attention typically centres on 'political' deep fakes. Often simulating the likeness of high-profile politicians, these videos are charged with spreading misinformation and triggering political instability. While those in power clamour to combat political deep fakes, their pornographic counterparts are becoming part of the scenery in cyberspace. Using source material from Twitter, this article explores the relationship between political and pornographic deep fakes, finding that they operate in similar ways to silence critical speech. This article recommends that responses to deep fakes address the underlying inequalities that lead this new technology to disproportionately target women.